COMPARATIVE ANALYSIS OF CHARACTERISTICS OF CADASTRAL SYSTEMS OF EUROPEAN UNION COUNTRIES - Meteshkin, К.; Pilicheva, М.; Masliy, L. (Municipal economy of cities. Series: «Economy science», 2023)
A modern cadastral system should include a legal, technical and economic component. The legal component determines information about owners and users taking into account the historical aspect of registration of property rights, the technical component should include data on the location of the land plot, its quantitative and qualitative indicators, and the economic component, in turn, forms an idea of the ways of using this land plot and its value. There are various types of land cadastral systems, which differ in their structure and functionality, so the study of their main characteristics is an urgent issue today. The purpose of this article is to determine the main characteristics and features of cadastral systems with the aim of improving the State Land Cadastre of Ukraine. Modern cadastral systems of the world are organized mainly by the land registration component. According to this feature, two main systems of securing rights to land ownership or real estate are distinguished: "Agreement system" and "Title system". The difference between the two concepts is related to the cultural development and judicial system of the country and is whether only the transaction is registered (deal system) or the title itself is registered and protected (title system). А comparative analysis of the developed and reliable European cadastral systems of Austria, Germany, Switzerland and France was performed. It was established that all considered cadastral systems have the same characteristics, such as: completeness and accuracy of geodata – presented in the form of a detailed cadastral map; accessibility and ease of use – access to cadastral systems is free and available to citizens; security level – modern technologies are used to protect data, including encryption and authentication of users; regularity of updates – usually once a year, and distinctive features, namely: variety of functions that they solve; various data collection systems are used; different level of integration with other systems.